199k views
0 votes
The function f(x) = x2 − 6x + 3 is transformed such that g(x) = f(x − 2). Find the vertex of g(x).

not C


(5, −6)

(5, −8)

(1, −6)

(3, −8)

2 Answers

2 votes

Answer:

A. (5, −6)

Step-by-step explanation:

I got it rigth on the test and props to the girl in the comment section :)

Have an amazing day fam!

User Maque J
by
5.6k points
4 votes

Answer: The vertex of g(x) is

( 1 , -6 )

Explanation:

g(x) = f(x − 2) and

f(x) = x2 − 6x + 3

Let X = x of f(x) and x = x of g(x)

Using function by substitution

X = x - 2

x = X+2

Please find the attached file for the remaining solution

The function f(x) = x2 − 6x + 3 is transformed such that g(x) = f(x − 2). Find the-example-1
User Alexander Bily
by
5.7k points